The development of Acid-Base Electronic Chemistry Comic Learning Media for High School Students - Agustina Atinia Halawa; Inelda Yulita; Nina Adriani (Journal of Science Education Research, 2022)
The development of Acid-Base electronic chemistry comic learning media for High School Students was developed to make it easier for students to learn chemistry subjects, especially Acid-Base materials. This study aimed to 1) Develop of Acid-Base Electronic Chemical Comic Learning Media for High School Students. 2) Find out the level of validity of the Acid-Base Electronic Chemical Comic Learning Media for High School Students, and 3) Find out the practicality of acid-base electronic chemical comic learning media for teacher and students Senior High School. This research was a research and development based on the Hanafin and Peck model which consists of three stages, namely needs analysis, design, and development and implementation. The results of analysis of the development of acid-base electronic chemical comic learning media for High School Students required the validity criteria with the results of the material expert test of 85% with a very valid category, the results of the media validity test getting a value of 78.57% with valid criteria. The results of the practicality test were obtained from the teacher's response of 88.6% with very practical criteria and 82.4% student response with very practical criteria. Based on the results of the study, it could be concluded that the develop of acid-base electronic chemical comic learning media for High School Students is valid and practical to use as learning media.